Certificateless Proxy Signature from RSA. (23rd June 2014) - Deng, Lunzhi; Zeng, Jiwen; Qu, Yunyun
Abstract : Although some good results were achieved in speeding up the computation of pairing function in recent years, it is still interesting to design efficient cryptosystems with less bilinear pairing operation. A proxy signature scheme allows a proxy signer to sign messages on behalf of an original signer within a given context. We propose a certificateless proxy signature (CLPS) scheme from RSA and prove its security under the strongest security model where the Type I/II adversary is a super Type I/II adversary.